SYMMETRY IN THE RELATIONSHIPS OF EXCHANGE - V. Kuligin (Вестник университета, 2016)
A thing going into sphere of exchange is transformed into a social phenomenon. Either of the things for all that is characterized by property of a duality. As a result of exchange a state its participants is changed. This change does not touch their essential characteristics. An invariance of structural elements of the exchange is remained. A maintenance of a form and condition the letters suggests retention of symmetry in the relationships of exchange.